2015
DOI: 10.1007/s11096-015-0199-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical medication reviews in elderly patients with polypharmacy: a cross-sectional study on drug-related problems in the Netherlands

Abstract: Background Knowledge of drug-related problems (DRPs) identified in the medication of home-dwelling elderly patients with polypharmacy has been based predominantly on medication reviews conducted in research settings rather than in daily practice. Objective To evaluate the prevalence of DRPs identified by means of a clinical medication review (CMR) and the implementation rate of proposed interventions in a large group of older patients with polypharmacy in the daily practice of community pharmacies. Setting 318… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 26 publications
(47 reference statements)
11
74
1
1
Order By: Relevance
“…As noted in the Introduction, Japan's public health insurance system recently began rewarding physicians with the payment of a medical adjustment fee upon their eliminating two or more medications in patients prescribed six or more oral medications. Many past studies reported a high CCI as a factor of polypharmacy . In the present study, the OR for the CCI was significant at 1.201.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…As noted in the Introduction, Japan's public health insurance system recently began rewarding physicians with the payment of a medical adjustment fee upon their eliminating two or more medications in patients prescribed six or more oral medications. Many past studies reported a high CCI as a factor of polypharmacy . In the present study, the OR for the CCI was significant at 1.201.…”
Section: Discussionsupporting
confidence: 55%
“…The current study investigated home‐care patients, who tend to be frail with multicomorbidity, and to have low cognitive status and low physical function status. These factors have reportedly been associated with an increased risk of polypharmacy . Therefore, the background characteristics of the participants in the current study tend to increase the risk of polypharmacy.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Polypharmacy (PP) also increases the prevalence of drug-related problems, such as drug-drug interactions, adverse drug reactions, prescription errors and non-adherence [10,11]. Though there is no consensus about the exact cut-off value for polypharmacy, usually it is defined as the concomitant use of more than or equal to 4-8 chronic medications [6,12,13].…”
Section: Introductionmentioning
confidence: 99%